2017
DOI: 10.1371/journal.pone.0182201
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Dispositional Flow: Validity and reliability of the Dispositional Flow State Scale 2, Italian version

Abstract: ObjectiveThe aim of this study is to evaluate the psychometric properties of the Italian version of the Dispositional Flow Scale-2 (DFS-2), for use with Italian adults, young adults and adolescents.MethodIn accordance with the guidelines for test adaptation, the scale has been translated with the method of back translation. The understanding of the item has been checked according to the latest standards on the culturally sensitive translation. The scale thus produced was administered to 843 individuals (of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
1
20
1
Order By: Relevance
“…The model with a second-order factor yielded indexes that were lower yet still within the expected parameters; it is thus also considered valid. Similar results were found in studies with the original scale and the Italian version of the scale (Riva et al 2017), in which both models demonstrated satisfactory fit according to confirmatory analysis. In the original scale, the nine-factor model also presented a slightly better fit than the second-order model did (Jackson et al 2010).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The model with a second-order factor yielded indexes that were lower yet still within the expected parameters; it is thus also considered valid. Similar results were found in studies with the original scale and the Italian version of the scale (Riva et al 2017), in which both models demonstrated satisfactory fit according to confirmatory analysis. In the original scale, the nine-factor model also presented a slightly better fit than the second-order model did (Jackson et al 2010).…”
Section: Discussionsupporting
confidence: 85%
“…However, there are no publications concerning those versions. More recently, the Italian version of the DFS-2 General (for adults, young people, and adolescents, in general contexts) was published (Riva et al 2017), and the authors verified its applicability beyond the field of sports. The DFS-2 Italian version is a valid, reliable instrument for also measuring flow in contexts involving study, work, leisure, and creative activities.…”
Section: Flow Measurementmentioning
confidence: 93%
“…However, Jackson and Csikszentmihalyi (1999) have described the merging of action and awareness as "the most telling aspect of the flow experience" (p. 20) in the domain of sport, indicating that either this aspect of flow may not be essential for the experience of flow in music performance, or that maybe "flow is not being experienced as often as high global flow scores suggest" (Sinnamon et al, 2012, p. 20). The DFS-2 is probably the most commonly used tool for investigating dispositional flow across a variety of domains (Riva et al, 2017), however these findings indicate that there is a need to carry out further investigations of the psychometric adequacy of the DFS-2 for measuring flow in the domain of music performance. It is suggested that the full 36-item measure be used (Jackson & Eklund, 2002) in such investigations, together with qualitative studies of the experiences of flow with performing musicians, in order to provide a detailed, finely grained picture of the contribution of each of the nine dimensions of flow to the experience of flow in the domain of music performance.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, the P Scale has been found to have robust psychometric properties as indicated by its good reliability coefficients (e.g., Caprara et al, 2012), its measurement invariance across gender and countries (e.g., Caprara et al, 2012; Heikamp et al, 2014), and its expected associations with theoretically relevant constructs such as positive and negative affect, depression, and personality traits (e.g., Caprara et al, 2012; Borsa et al, 2015; Tian et al, 2018). Recent findings also attested to the convergent validity of the P Scale with implicit measures of positivity (using the implicit association test), self-perceived intelligence (Costantini et al, 2019), and dispositional flow (Riva et al, 2017).…”
Section: Introductionmentioning
confidence: 86%